The progesterone and estrogen modify the uterine prolactin and prolactin receptor expression of hyperprolactinemic mice. (February 2015) - do Amaral, Vinícius Cestari; Carvalho, Kátia Candido; Maciel, Gustavo Arantes Rosa; Simoncini, Tommaso; da Silva, Priscilla Ludovico; Marcondes, Rodrigo Rodrigues; Soares, José Maria; Baracat, Edmund Chada
Abstract The aim of this study was to evaluate the effects of metoclopramide-induced hyperprolactinemia on the prolactin (PRL) and PRL receptor's expression in the uterus of mice. For this purpose, 49 Swiss mice were divided into the following groups: GrSS (non-ovariectomized mice given vehicle); GrMET (non-ovariectomized mice treated with metoclopramide); OvSS (ovariectomized mice given vehicle); OvMET (ovariectomized mice treated with metoclopramide); OvMET+17βE (ovariectomized mice treated with metoclopramide and 17β estradiol); OvMET+MP (ovariectomized mice treated with metoclopramide and micronized progesterone); OvMET+17βE+MP (ovariectomized mice treated with metoclopramide and a solution of 17β estradiol and micronized progesterone). Immunohistochemical analyzes were evaluated semi-quantitatively. Our results showed that GrMET, OvMET+MP, and OvMET+17βE+MP presented strong PRL expression. OvMET and OvMET+17βE presented mild reaction, while GrSS and OvSS presented weak reaction. Concerning PRL receptor, OvMET+MP and OvMET+17βE+MP showed strong reaction; GrMET, OvSS, and OvMET+17βE showed mild reaction; and GrSS and OvMET showed weak reaction. These findings suggest that progesterone alone or in combination with estrogen may increase the expression of uterine PRL and PRL receptor.